Rural futures for young adults: Rural development and regeneration in the Netherlands - Koreman, Maarten (A+BE | Architecture and the Built Environment, 2024)
Over the past decades, rural municipalities in Europe have been changing. While the population of urban municipalities is increasing, the population of rural municipalities is decreasing and ageing. Especially young adults are moving from rural towards urban municipalities. However, these young adults are essential in creating rural development and regeneration in rural municipalities. The roles of communities and governance in rural municipalities in Europe have also changed during the past decades. The responsibilities for rural development have decentralised to lower levels of government, communities, and individuals. Meanwhile, the economic development of European rural municipalities shows continued farm enlargement and a trend towards a more diversified rural economy, with fewer people working in agriculture. Regarding all these changes, it is important to understand what young adults want to do and can do to support rural development and regeneration. This dissertation uses the Netherlands as a case study to investigate the future of young adults in rural municipalities. Demographically, the Netherlands is strongly urbanized and densely populated. Inhabitants of urban municipalities are relatively younger than inhabitants of rural municipalities, where more population decline is expected. Meanwhile, decentralisation is the leading governmental development in the Netherlands. In response to their increased number of tasks, many small, rural municipalities in the Netherlands have been amalgamated into more urban municipalities or have been merged. Therefore, rural municipalities in the Netherlands can sometimes be considered rural regions. Like the European level, the economic structure of rural municipalities in the Netherlands will continue to go through a quick transition, invoking discussion on rural economic planning and how to use scarce land. The economic restructuring of the countryside and the decentralisation of governmental tasks in the Netherlands may also relate to its rural political geography. Electoral results show increased political discontent among inhabitants of rural municipalities in the Netherlands. This context leads to questions on future opportunities for young adults in these places.